Tebentafusp in combination with durvalumab and/or tremelimumab in patients with metastatic cutaneous melanoma: a phase 1 study - Hamid, Omid; Hassel, Jessica C.; Shoushtari, Alexander N.; Meier, Friedegund; Bauer, Todd M.; Salama, April K. S.; Kirkwood, John M.; Ascierto, Paolo A.; Lorigan, Paul C.; Mauch, Cornelia; Orloff, Marlana; Evans, Thomas R. Jeffry; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Background Immune checkpoint inhibitors have significantly improved outcomes in first line cutaneous melanoma. However, there is a high unmet need for patients who progress on these therapies and combination therapies are being explored to improve outcomes. Tebentafusp is a first-in-class gp100×CD3 ImmTAC bispecific that demonstrated overall survival (OS) benefit (HR 0.51) in metastatic uveal melanoma despite a modest overall response rate of 9%. This phase 1b trial evaluated the safety and initial efficacy of tebentafusp in combination with durvalumab (anti-programmed death ligand 1 (PDL1)) and/or tremelimumab (anti-cytotoxic T lymphocyte-associated antigen 4) in patients with metastatic cutaneous melanoma (mCM), the majority of whom progressed on prior checkpoint inhibitors. - Methods In this open-label, multicenter, phase 1b, dose-escalation trial, HLA-A*02:01-positive patients with mCM received weekly intravenous tebentafusp with increasing monthly doses of durvalumab and/or tremelimumab starting day 15 of each cycle. The primary objective was to identify the maximum tolerated dose (MTD) or recommended phase 2 dose for each combination. Efficacy analyses were performed in all tebentafusp with durvalumab±tremelimumab treated patients with a sensitivity analysis in those who progressed on prior anti-PD(L)1 therapy. - Results 85 patients were assigned to receive tebentafusp in combination with durvalumab (n=43), tremelimumab (n=13), or durvalumab and tremelimumab (n=29). Patients were heavily pretreated with a median of 3 prior lines of therapy, including 76 (89%) who received prior anti-PD(L)1. Maximum target doses of tebentafusp (68 mcg) alone or in combination with durvalumab (20 mg/kg) and tremelimumab (1 mg/kg) were tolerated; MTD was not formally identified for any arm. Adverse event profile was consistent with each individual therapy and there were no new safety signals nor treatment-related deaths. In the efficacy subset (n=72), the response rate was 14%, tumor shrinkage rate was 41% and 1-year OS rate was 76% (95% CI: 70% to 81%). The 1-year OS for triplet combination (79%; 95% CI: 71% to 86%) was similar to tebentafusp plus durvalumab (74%; 95% CI: 67% to 80%). - Conclusion At maximum target doses, the safety of tebentafusp with checkpoint inhibitors was consistent with safety of each individual therapy. Tebentafusp with durvalumab demonstrated promising efficacy in heavily pretreated patients with mCM, including those who progressed on prior anti-PD(L)1. - Trial registration number NCT02535078.
Accepted 12 May 2023
Gesehen am 29.08.2023